1990
DOI: 10.2165/00003495-199039060-00008
|View full text |Cite
|
Sign up to set email alerts
|

Pinacidil

Abstract: Pinacidil is an orally administered antihypertensive drug that acts via direct relaxation of vascular smooth muscle to produce peripheral vasodilatation and a reduction in blood pressure without significant direct effects on cardiac electrophysiology. Pinacidil is unrelated to other antihypertensive drugs in clinical use, either in structure or mechanism of action. It belongs to a new class of agents called 'potassium channel openers' which act via potassium efflux to hyperpolarize cell membranes, indirectly c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(11 citation statements)
references
References 87 publications
1
10
0
Order By: Relevance
“…In particular, the maximum plasma concentrations after the last dose, the area under the plasma concentration curve in the interval between doses at steady-state and the mean residence time met Westlake's statistical criteria for bioequivalence (> 20 %). Whereas most of the pharmacokinetic parameters were also similar to those previously measured after single oral doses [2,7]. the values of the half-life of elimination were greater than those we found after single administration of the same oral dose to healthy subjects [7].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In particular, the maximum plasma concentrations after the last dose, the area under the plasma concentration curve in the interval between doses at steady-state and the mean residence time met Westlake's statistical criteria for bioequivalence (> 20 %). Whereas most of the pharmacokinetic parameters were also similar to those previously measured after single oral doses [2,7]. the values of the half-life of elimination were greater than those we found after single administration of the same oral dose to healthy subjects [7].…”
Section: Discussionsupporting
confidence: 83%
“…Venous blood samples were drawn at the following times: on the morning of days 0, 1, 2, 3, 4, 5, 6, and at the following times on day 7: 0 (immediately before the drug administration), 0.5, 1, 2, 3, 4, 6, 8, 12, 24 and 36 h after drug administration. The sampling schedule was selected on the basis of previous human pharmacokinetic studies [2,7]. Blood samples (5 ml) were drawn by venipuncture from antecubital veins and collected into two plastic tubes containing heparin and centrifuged (within 5 min) at 4 °C at 1200 x g for 10 min.…”
Section: Subjects and Experimental Designmentioning
confidence: 99%
“…KCOs have not been associated with tachyphylaxis to the antihypertensive effect or rebound hypertension on abrupt withdrawal [98]. Vegh reported that one particular KCO given at one dose level and administered by a particular route is unlikely to increase the risk of ventricular fibrillation under conditions of myocardial ischemia or reperfusion unless marked systemic antihypertension occurs [99].…”
Section: Effects Of Kcos On the Cardiovascular Systemmentioning
confidence: 99%
“…In contrast, the compound (94) with a methyl group decreases the potassium currents, whereas the compounds with benzyl or 2-hydroxy-5-chlorobenzyl groups have no effects on the potassium currents. Analysis of (84), (90), and (98) indicates that for the carbonyl on the branched substituent group of the 2,3 and 4-position, the order of intensity of changes in the potassium current is (90) > (84) > (98).…”
Section: )mentioning
confidence: 99%
“…K ATP channel openers are already in clinical use for various non-ocular disorders including systemic hypertension and ischemic heart diseases. [ 42 45 ] Recently, we have shown that several major K ATP channel openers (e.g. diazoxide, nicorandil) have ocular hypotensive properties in human and animal model systems.…”
Section: Introductionmentioning
confidence: 99%